Delayed breastfeeding initiation and infant survival: A systematic review and meta-analysis - Smith, Emily R.; Hurt, Lisa; Chowdhury, Ranadip; Sinha, Bireshwar; Fawzi, Wafaie; Edmond, Karen M.; on behalf of the Neovita Study Group (PLOS ONE, 2017)
Objective To assess the existing evidence regarding breastfeeding initiation time and infant morbidity and mortality. Study design We conducted a systematic review and meta-analysis. We searched Pubmed, Embase, Web of Science, CINAHL, Popline, LILACS, AIM, and Index Medicus to identify existing evidence. We included observational studies and randomized control trials that examined the association between breastfeeding initiation time and mortality, morbidity, or nutrition outcomes from birth through 12 months of age in a population of infants who all initiated breastfeeding. Two reviewers independently extracted data from eligible studies using a standardized form. We pooled effect estimates using fixed-effects meta-analysis. Results We pooled five studies, including 136,047 infants, which examined the association between very early breastfeeding initiation and neonatal mortality. Compared to infants who initiated breastfeeding ≤1 hour after birth, infants who initiated breastfeeding 2–23 hours after birth had a 33% greater risk of neonatal mortality (95% CI: 13–56%, I2 = 0%), and infants who initiated breastfeeding ≥24 hours after birth had a 2.19-fold greater risk of neonatal mortality (95% CI: 1.73–2.77, I2 = 33%). Among the subgroup of infants exclusively breastfed in the neonatal period, those who initiated breastfeeding ≥24 hours after birth had an 85% greater risk of neonatal mortality compared to infants who initiated <24 hours after birth (95% CI: 29–167%, I2 = 33%). Conclusions Policy frameworks and models to estimate newborn and infant survival, as well as health facility policies, should consider the potential independent effect of early breastfeeding initiation.